The perspective of key stakeholders on the sustainable design of reverse logistics in e-commerce: an interpretive sensemaking review - Iria González Romero; Ángel Ortiz Bas; J. Carlos Prado Prado (International Journal of Production Management and Engineering, 2025)
The uncontrolled rise of returns in e-commerce has become a challenge for supply chains and key stakeholders (e-retailers, customers, transport companies and institutions). Literature, however, has not yet offered a systematic understanding of this subject. In this context, this article aims to better comprehend sustainable reverse logistics by defining the elements involved and the stakeholders' perspective. To do so, a systematic literature review is carried out through a sensemaking interpretative review, defining seven elements of sustainable reverse logistics (return policy, return location, demand and return location density, validation point, return destination, transportation strategy and information management). Furthermore, the perspective of each stakeholder is presented. In this sense, e-retailers, as ultimate decision-makers, are involved in all seven elements. When this process is outsourced, transport companies also have an impact on all relevant elements. Customers have an impact on almost all elements, as they demand a high level of service. Institutions, as regulators seeking more sustainable cities, apply measures that influence almost all relevant elements. This analysis also highlights the importance of collaboration between stakeholders, as well as specific gaps in the literature. Finally, this research provides a suitable tool for managers to establish sustainable reverse logistics that meets the preferences of each stakeholder.